Hubungan Pendidikan dan Dukungan Keluarga Dengan Kecemasan Ibu Hamil PrimigravidaTrimester III Menjelang Proses Persalinan - Yuldensia Avelina; Theresia Syrilla Da Cunha; Albertha Sintya Key Timu (Peneliti.net, 2023)
Pregnancy is a natural thing that happens to produce women. When a mother finds out that she is pregnant, she will feel very happy because this is the happiest and most awaited time, but when experiencing the process of pregnancy a mother will experience anxiety due to pregnancy and childbirth. Anxiety is one of the psychological disorders that often occurs in pregnant women, which is more present in the third trimester of pregnancy. Anxiety in pregnant women can have a negative impact on both the mother and the fetus. This study aimed to explain the relationship between education and family support on the anxiety of third times trimester pregnant women in the Waipare Health CenterThe research design used is analytic correlation with a cross sectional approach. The population in this study were all third-trimester primigravida pregnant women in the working area of the Waipare Health Center who were taken using the total sampling technique and totaling 24 respondents. Data collection uses a questionnaire and is tested using the Lambda and Gamma tests.The results showed that there was a relationship between education and anxiety levels (p-value = 0.000), there was a relationship between family support and anxiety levels (p-value = 0.006). Based on the results of the research above, it is hoped that health workers will provide education to mothers to reduce anxiety in facing childbirth so as to reduce the high risk of maternal and infant mortality.